Multi-professional care for the patient affected by pemphigus vulgaris (Research, Society and Development, 2020)
Patients suffering from pemphigus vulgaris need specialized care. Thus, in their comprehensive care, multi-professional action is essential to meet the different technical challenges of the disease. The objective was to report a case of pemphigus vulgaris and multi-professional performance. This is a descriptive study of the case report of a patient seen at a referral hospital for pemphigus. The information necessary to describe the case was collected after approval by the Research Ethics Committee. The patient arrived at the hospital with diffuse crusty lesions with associated pruritus throughout the body for approximately two months. After clinical evaluation and laboratory examination, the histological examination found the presence of a supra-basal intraepidermal bubble, with the presence of acantholytic cells inside the bubble, concluding as pemphigus vulgaris. During hospitalization, the patient had several secondary infections, used corticosteroids, analgesics, polyantibiotic therapy, and immunoglobulin. At the end of 78 days of hospitalization, he developed complications and died. Early diagnosis and the start of rapid treatment delay the evolution of the disease, improving the appearance of the lesions, which reduces the length of hospital stay and the risk of infections occurring. Therefore, the performance of the multi-professional team contributes to solving the challenges related to the disease, such as improvement in physical, emotional, nutritional, and patient safety. We emphasize measures for the prevention and control of infections, such as, for example, hand hygiene by all professionals, the use of personal protective equipment in the management of the patient, and adequate hygiene of the environment.